Emerging Risk Factors and Prevention of Perioperative Pulmonary Complications - Priyanka Bhateja; Roop Kaw (The Scientific World Journal)
Modern surgery is faced with the emergence of newer “risk factors” and the challenges associated with identifying and managing these risks in the perioperative period. Obstructive sleep apnea and obesity hypoventilation syndrome pose unique challenges in the perioperative setting. Recent studies have identified some of the specific risks arising from caring for such patients in the surgical setting. While all possible postoperative complications are not yet fully established or understood, the prevention and management of these complications pose even greater challenges. Pulmonary hypertension with its changing epidemiology and novel management strategies is another new disease for the surgeon and the anesthesiologist in the noncardiac surgical setting. Traditionally most such patients were not considered surgical candidates for any required elective surgery. Our review discusses these disease entities which are often undiagnosed before elective noncardiac surgery.